A One Health evaluation of water, sanitation, and hygiene (WASH) services in Butaro Sector, Rwanda. (18th February 2022) - Coughlin, Laura L.; Schurer, Janna M.; Umubyeyi, Carene; Sijenyi, Salome; Arif, Khurram; Niyonkuru, Vivianne Umuhire; Byiringiro, Emmanuel; Lutz, Naomi; Korukire, Noel; Murcott, Susan; Amuguni, Hellen J.
Abstract: In 2018, rural residents of northern Rwanda raised water, sanitation, and hygiene (WASH) access and availability as a community concern; however, no baseline information was available to prioritize communities for intervention. This study aimed to assess WASH for people and animals in four cells in Butaro Sector and to identify the cell with the lowest WASH access. This cross-sectional, quantitative study utilized telephone surveys to collect data. Households were randomly selected, and 539 male and female heads-of-household agreed to participate. Overall, 56.8% of households reported access to safe drinking water, but this differed significantly by cell ( p < 0.001). Approximately half (54.2%) of respondents walked 30 min or longer to fetch water, travelling one or more times per day. Nearly all (98.5%) households reported the presence of sanitation infrastructure, most often a pit latrine. Across cells, animals experienced poorer access to clean water and sanitation than people. One cell, Gatsibo, reported the poorest overall access to WASH services. Multi-sector collaboration among public health, water authorities, and local leaders is needed to reduce travel times for fetching water and to ensure that all residents can access sufficient safe water to meet the health and hygiene needs of people and animals. HIGHLIGHTS: Human, animal, and environmental factors relating to human and animal WASH were characterized in four cells in Butaro Sector, Rwanda. Important gaps were identified in access to safe drinking water, including long travel times to water sources and barriers to water treatment. Gatsibo was identified to have the poorest overall access to WASH services for human and animal residents. Graphical Abstract